Styrylsulfonates and ‐Sulfonamides through Pd‐Catalysed Matsuda–Heck Reactions of Vinylsulfonic Acid Derivatives and Arenediazonium Salts. Issue 17 (25th May 2016) - Schmidt, Bernd; Wolf, Felix; Brunner, Heiko
Abstract : Arene diazonium salts undergo Matsuda–Heck reactions with vinylsulfonates and ‐sulfonamides to give styrylsulfonic acid derivatives in high to excellent yields and with high to excellent selectivities. By quantifying the evolution of nitrogen over time in a gas‐meter apparatus, the reactivities of ethylvinylsulfonate and the benchmark olefin methyl acrylate were compared for an electron‐rich and an ‐deficient arene diazonium salt. Tertiary sulfonamides react in Matsuda–Heck couplings with high conversions, but require long reaction times, which prevents the determination of kinetic data through the measurement of nitrogen evolution. Secondary sulfonamides were found to be unreactive. From these results, the following order of reactivity could be deduced: H2 C=CHCO2 Me > H2 C=CHSO2 OEt > H2 C=CHSO2 N(Me)Bn >> H2 C=CHSO2 NHBn. Through the Matsuda–Heck coupling of 5‐indolyldiazonium salt and a tertiary vinylsulfonamide, the synthesis of the C‐5‐substituted indole part of the antimigraine drug naratriptan was accomplished in high yield. Abstract : Diazonium salts undergo efficient Pd‐catalysed couplings with vinylsulfonic acid derivatives under ligand‐free and base‐free conditions with Pd(OAc)2 as the precatalyst. The reactivities of vinylsulfonates and ‐sulfonamides were compared quantitatively with the benchmark olefin methyl acrylate. The synthesis of a precursor of the antimigraine drug naratriptan highlights the utility of the method.